The endocrine management of intractable masturbation after epilepsy surgery: a case report and literature review. Issue 11 (October 2019) - Ebere, Ikenna; Staufenberg, Ekkehart FA; Dhatariya, Ketan K
Lesson: Intractable masturbation has been reported after epilepsy surgery and can be difficult to control, we present a case treated with cyproterone acetate and haloperidol to achieve an endocrine based resolution of symptoms.